1988
DOI: 10.1097/00000658-198809000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Dermis for Major Burns

Abstract: This communication presents an 11-center prospective randomized trial using the artificial dermis invented by Burke and Yannas. Patients with life-threatening burns who underwent primary excision and grafting within 7 days of injury had comparable sites randomized to receive either the artificial dermis (study site) or the investigator's usual skin grafting material (control site). Control materials were autograft, allograft, xenograft, or a synthetic dressing. Epidermal grafts were applied to the study site d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 616 publications
(99 citation statements)
references
References 13 publications
0
98
0
1
Order By: Relevance
“…It is known that collagen is a structural protein that is said to be one of the most suitable materials for constructing artificial substitutes for diseased or damaged tissues and organs [15]. Collagens combined with proteoglycans have been reported to be metabolically stable when implanted in vivo and have been used as artificial skin, which accelerates the wound healing [16]. Chitosan, an amino-polysaccharide (poly(1,4-D-glucosamine)) derived from chitin by deacetyation, has been widely applied in biomedical applications, such as wound dressings and drug-delivery systems [17,18] on account of its non-toxic and biocompatible nature.…”
Section: Hepatocyte Culturementioning
confidence: 99%
“…It is known that collagen is a structural protein that is said to be one of the most suitable materials for constructing artificial substitutes for diseased or damaged tissues and organs [15]. Collagens combined with proteoglycans have been reported to be metabolically stable when implanted in vivo and have been used as artificial skin, which accelerates the wound healing [16]. Chitosan, an amino-polysaccharide (poly(1,4-D-glucosamine)) derived from chitin by deacetyation, has been widely applied in biomedical applications, such as wound dressings and drug-delivery systems [17,18] on account of its non-toxic and biocompatible nature.…”
Section: Hepatocyte Culturementioning
confidence: 99%
“…Multi-center randomized clinical trials of 106 patients compared matched pairs of wounds covered with (a) artificial dermis with wounds covered with (b) meshed STSGs, allografts, xenografts, or synthetic dressings. The artificial dermis was sutured or stapled in place, and, following vascular ingrowth, usually in 14 days, was grafted with epidermis taken at the thinnest dermatome setting that would produce a translucent graft with minimal dermis attached (Heimbach et al, 1988). The following were the major advantages of this artificial skin with thin epithelial grafts as compared with meshed split-thickness skin grafts or allografts:…”
Section: (All) In Vitro Tissue Engineering Of the Dermismentioning
confidence: 99%
“…They reduced contraction and scar formation with improvement of extracellular matrix remodeling and elastin regeneration [7,8]. In trials in burned patients was demonstrated significant skin regeneration using the same scaffold [9,10]; a limited numbers of randomized controlled trials that study skin substitutes have been published, but the evidence of studies is encouraging. Among skin substitutes, the dermal substitutes can be manufactured in high quantity with low price, easy to keep and to use.…”
Section: Short Commentarymentioning
confidence: 99%